Monitoring peptide tyrosine nitration by spectroscopic methods - Niederhafner, Petr; Šafařík, Martin; Neburková, Jitka; Keiderling, Timothy A; Bouř, Petr; Šebestík, Jaroslav (Amino acids, 2021)
Oxidative stress can lead to various derivatives of the tyrosine residue in peptides and proteins. A typical product is 3-nitro-L-tyrosine residue (Nit), which can affect protein behavior during neurodegenerative processes, such as those associated with Alzheimer's and Parkinson's diseases. Surface enhanced Raman spectroscopy (SERS) is a technique with potential for detecting peptides and their metabolic products at very low concentrations. To explore the applicability to Nit, we use SERS to monitor tyrosine nitration in Met-Enkephalin, rev-Prion protein, and α-synuclein models. Useful nitration indicators were the intensity ratio of two tyrosine marker bands at 825 and 870 cm-1 and a bending vibration of the nitro group. During the SERS measurement, a conversion of nitrotyrosine to azobenzene containing peptides was observed. The interpretation of the spectra has been based on density functional theory (DFT) simulations. The CAM-B3LYP and ωB97XD functionals were found to be most suitable for modeling the measured data. The secondary structure of the α-synuclein models was monitored by electronic and vibrational circular dichroism (ECD and VCD) spectroscopies and modeled by molecular dynamics (MD) simulations. The results suggest that the nitration in these peptides has a limited effect on the secondary structure, but may trigger their aggregation.
Keywords: tyrosin; Electronic circular dichroism (ECD); simulace molekulární dynamiky; cirkulární dichroismus; Ramanova spektroskopie; Spectrum Analysis, Raman; Density functional theory (DFT); Tyrosine; azosloučeniny; Density Functional Theory; Circular Dichroism; Oxidative stress; Peptides; sekundární struktura proteinů; Nitration; peptidy; Surface-enhanced Raman spectroscopy (SERS); Protein Structure, Secondary; teorie funkcionálu hustoty; Azo Compounds; Molecular Dynamics Simulation; Vibrational circular dichroism (VCD)